Tungsten carbide nanoparticles show a broad spectrum virucidal activity against enveloped and nonenveloped model viruses using a guideline‐standardized in vitro test. (11th September 2019) - Pfaff, F.; Glück, B.; Hoyer, T.; Rohländer, D.; Sauerbrei, A.; Zell, R.
Abstract: Five tungsten carbide nanoparticle preparations (denoted WC1‐WC5) were investigated for broad spectrum virucidal activity against four recommended model viruses. These are modified vaccinia virus Ankara (MVA), human adenovirus type 5 (HAdV‐5), poliovirus type 1 (PV‐1) and murine norovirus (MNV). All virucidal tests were performed two to five times using the quantitative suspension test, which is a highly standardized test method to evaluate the virucidal efficacy of disinfectants in accordance with the European norm EN 14476+A1 and the German DVV/RKI guidelines. Quantitative detection of viruses was conducted by endpoint titration and quantitative real‐time PCR. Results showed that three of the five tested compounds (WC1‐WC3) were able to reduce the infectivity of all model viruses by at least four log10 of tissue culture infective dose 50% per ml after 15 min, whereas the other two compounds exhibited only limited efficacy (WC4) or showed cytotoxicity (WC5). Virucidal activity of nanoparticles increased with incubation time and a dose‐effect curve showed dependence of virucidal activity with particle concentration. Whereas WC1‐WC4 showed little cytotoxicity, WC5 which was doped with copper exhibited a significant cytotoxic effect. These findings propose tungsten carbide nanoparticles to be very promising in terms of new disinfection techniques. Significance and Impact of the Study: The present study investigates the virucidal activity of tungsten carbide nanoparticles using the quantitative suspension test in accordance with the European norm EN 14476+A1 and the German DVV/RKI guidelines. Due to highly standardized assay conditions, results of this test are considered very reliable for evaluation of the virucidal activity of disinfectants. Broad‐spectrum activity and high efficacy of three different tungsten carbide nanoparticles preparations is concluded. Abstract : Significance and Impact of the Study: The present study investigates the virucidal activity of tungsten carbide nanoparticles using the quantitative suspension test in accordance with the European norm EN 14476+A1 and the German DVV/RKI guidelines. Due to highly standardized assay conditions, results of this test are considered very reliable for evaluation of the virucidal activity of disinfectants. Broad‐spectrum activity and high efficacy of three different tungsten carbide nanoparticles preparations is concluded.